Hippo Signaling Pathway Involvement in Osteopotential Regulation of Murine Bone Marrow Cells Under Simulated Microgravity - Ekaterina Tyrina; Danila Yakubets; Elena Markina; Ludmila Buravkova (Cells)
The development of osteopenia is one of the most noticeable manifestations of the adverse effects of space factors on crew members. The Hippo signaling pathway has been shown to play a central role in regulating the functional activity of cells through their response to mechanical stimuli. In the present study, the components of the Hippo pathway and the protective properties of osteodifferentiation inducers were investigated under simulated microgravity (smg) using a heterotypic bone marrow cell culture model, which allows for the maintenance of the close interaction between the stromal and hematopoietic compartments, present in vivo and of great importance for both the fate of osteoprogenitors and hematopoiesis. After 14 days of smg, the osteopotential and osteodifferentiation of bone marrow stromal progenitor cells, the expression of Hippo cascade genes and the immunocytochemical status of the adherent fraction of bone marrow cells, as well as the paracrine profile in the conditioned medium and the localization of Yap1 and Runx2 in mechanosensitive cells of the bone marrow were obtained. Simulated microgravity negatively affects stromal and hematopoietic cells when interacting in a heterotypic murine bone marrow cell culture. This is evidenced by the decrease in cell proliferation and osteopotential. Changes in the production of pleiotropic cytokines IL-6, GROβ and MCP-1 were revealed. Fourteen days of simulated microgravity induced a decrease in the nuclear translocation of Yap1 and the transcription factor Runx2 in the stromal cells of the intact group. Exposure to osteogenic induction conditions partially compensated for the negative effect of simulated microgravity. The data obtained will be crucial for understanding the effects of spaceflight on osteoprogenitor cell growth and differentiation via Hippo–Yap signaling.